Gender matters in global politics : a feminist introduction to international relations - Shepherd, Laura J. (Oxon, London : Routledge, 2015)
"Gender Matters in Global Politics 2nd edition is a comprehensive textbook for advanced undergraduates studying feminism & international relations, gender and global politics and similar courses. It provides students with an accessible but in-depth account of the most significant theories, methodologies, debates and issues"--Provided by publisher
1. Theory/practice -- 2. Ethics and subjectivity -- 3. Violence and security -- 4. Political economy -- 5. International institutions -- 6. Identities, orders, borders -- 7. Information, communication, technology
Includes bibliographical references (p. 407-476) and index
Keywords: Feminism; Feminist theory; International relations